Optimization, kinetic modeling, and characterization of hydro-distillation and subcritical water extraction of Aquilaria malaccensis lamk leaves and wood essential oil - Samadi, Mahtab (2017)
Aquilaria malaccensis (gaharu), which is an Indo-Malaysian evergreen tree, is one of the most important higher-plants in south East Asia. Because of the high-demand for this valuable tree especially for its resinous wood oil, Aquilaria malaccensis is considered as an endangered species. On the other hand, the current extraction method (distillation) in gaharu industries not only requires lots of wood material for only small amount of essential oil, but also, it consumes lots of time and energy. Therefore, finding an efficient alternative to traditional distillation method such as Subcritical Water Extraction (SCWE; an extraction method that uses water at subcritical conditions) can make a significant difference in saving the materials, time, and energy. Thereby, the primary goal of this study was to assess whether SCWE can be used as an alternative to HD for extraction of A. malaccensis wood essential oil. In addition, this study, for the first time, aimed to analyze A. malaccensis leaves oil since not only there had been some indications that the leaves of this evergreen tree may be as valuable as its wood, but also, the positive outcome would put a stop to the waste of A. malaccensis leaves. For comparing both extraction methods (i.e. SCWE and HD), at first, the optimum conditions for both methods were identified by assessing the effect of different influential parameters (temperature/heating-power, sample-to-solvent ratio, and time). Hydro-distillation experiments conducted using clevenger apparatus, while SCWE was done using a batch subcritical reactor. Yield comparison between the essential oils extracted by HD and SCWE at optimum conditions showed that the yield of both leaves and wood essential oils extracted by SCWE (30 min) were almost 2.5 times the yield of HD (4-16 hrs). Additionally, the characterization tests were carried out on the essential oils and the leaves/wood samples. GC/MS results provided evidence that the quality of A. malaccensis wood and leave oils extracted by SCWE is significantly better compared to that extracted by HD as the amount of oxygenated and sesquiterpenoid compounds was found to be higher in oils extracted by SCWE. The essential oils extracted by SCWE also contained several value-added compounds useful in medicine such as furfural and guaiacol. FTIR, SEM, and BET/BJH on the wood and leaves samples provided further evidence for better performance of SCWE, since the sample’s pores, cell walls, cellulose, and hemicellulose were more damaged compared to those in HD sample. Furthermore, in this study, kinetic modelling was conducted in order to provide a better understanding of both HD’s and SCWE’s mechanism. The result of kinetic modelling indicated that the unsteady-state diffusion model is the best model for describing HD, whereas, two-site kinetic desorption and second-order model were found to be the best models for explaining SCWE of wood and leaves essential oils respectively. In short, the result of this study showed that SCWE is a better extraction method in terms of time, efficiency and quality. Both A. malaccensis leaves and wood oils were found to contain beneficial compounds useful for producing pesticides and medicine.